Como as cooperativas de crédito afetam a rentabilidade dos bancos comerciais brasileiros? - Gonzaga, André Lucas Moreira Gonzaga (Brasil, 2023)
We investigated the effects of the growth of credit unions, which by law are non-profit entities, on the return on assets e equity of Brazilian commercial banks. We also assess the effects on commercial banks’ main revenue e expense lines. Data from 2000 to 2021 were used e dynamic panel models, System-GMM, were estimated. The results indicate that the greater the relative participation of credit unions, the greater the return on assets e equity of commercial banks. As for the impact on expenses, we noticed that the greater the participation of credit unions, the lower the expenses with commercial bank funding. The results are robust for several specifications.